Analisis Kinerja Pegawai Dalam Meningkatkan Produktivitas Pada Unit Pelaksana Teknis Pengelolaan Saluran Air Limbah Kota Yoyakarta - Samingan Samingan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine employee performance and productivity in the Employee Performance Analysis in Increasing Productivity in the Yoyakarta City Waste Water Channel Management Technical Implementation Unit; To find out efforts to increase employee productivity in the Employee Performance Analysis in Increasing Productivity in the Yoyakarta City Waste Water Channel Management Technical Implementation Unit; and To determine the inhibiting and supporting factors for employee performance in the Employee Performance Analysis in Increasing Productivity in the Yoyakarta City Waste Water Channel Management Technical Implementation Unit. The data collection method was carried out by means of field research consisting of observation, in-depth interviews and documentation. The type of research used is descriptive qualitative analysis. From the research results it is known that employee competence in improving performance in Employee Performance Analysis in Increasing Productivity in the Yoyakarta City Waste Water Channel Management Technical Implementation Unit has increased based on the concepts of good performance, namely productivity, responsibility and discipline in accordance with applicable regulations. Based on the research results, it was concluded that employee productivity. Employee Performance Analysis in Increasing Productivity in the Yoyakarta City Waste Water Channel Management Technical Implementation Unit increased based on good performance concepts.